Numerical analysis on wave generated by the Qianjiangping landslide in Three Gorges Reservoir, China - Yin, Yue-ping; Huang, Bolin; Chen, Xiaoting; Liu, Guangning; Wang, Shichang (Landslides, 2015)
The Qianjiangping landslide occurred on July 13, 2003 when water level in the Three Gorges Reservoir in China reached 135 m a.s.l. for about 1 month. Thirteen people on the slope and 11 fishermen on boats in the nearby area were killed by this landslide and its wave. As a typical case, the Qianjiangping landslide is researched extensively, but the wave itself was studied much less. In this paper, a fluid–solid coupling model based on general moving objects (GMO) collision model and renormalisation group (RNG) turbulent model were employed, simplifying the sliding motion of the Qianjiangping landslide as a rigid body circular motion whose validity was verified by comparing with actual survey conditions related. Numerical simulation analysis shows that in the Qianjiangping landslide event, the solid–fluid energy-transferring rate was 5.97 %, while the motion of sliding mass could push and raise water body. The maximum-modelled wave run-up generated by the Qianjiangping landslide was 40.4 m (up to 175.4 m a.s.l.), while the maximal observed one was 39 m. It was the solitary wave, and the wave celerity was 32∼36 m/s or so. The hazardous river length of impulse wave was estimated to be 12.6 km, where wave height was more than 1 m high. The fluid–solid coupling numerical model employed by this paper can provide important reference for wave generated by other landslides around the world. Research of the landslide-generated wave is very significant in landslide hazard reduction and prevention.